USE OF INFORMATION ABOUT STATE VECTOR OF EXECUTIVE DEVICE IN STABILIZING SYSTEM OF A ROCKET ROTATION MOTION - Avdejev, V. V. (Radio Electronics, Computer Science, Control, 2018)
Context. A method for obtaining estimates of the dependence of stability factor and reduced work during the transient process for compensation of a constant disturbing acceleration on the presence in law of control data about current kinematic parameters of the executive device under condition of ensuring a prescribed static error is developed. It will give a possibility to take decision about level of complexity for appropriate units in stabilizing system. Objective. The purpose of the research is to estimate the influence of the law of control reduction by means of exclusion from one the data about state vector of the executive device on requirements to its power and stability factor. Method. A linear stationary in the vicinity of a certain point of the trajectory model of a plane rotational motion of a rocket for space purposes has been adopted, with taking into account the inertia of the executive device. Estimation of the stability factor is carried out on the plane of the roots of the characteristic polynomial and two coefficients of the law of control. Divided to the square of constant perturbation acceleration, the work of the executive device is determined by analytical solution of the differential equations of perturbed rotational motion in one of the stabilization planes. For statically stable and unstable rocket the dependence examples of the named performances on coefficients of the law of control by coordinates of the state vector are made. Results. For the application of the rocket for space purposes for the first time the dependence of the named indices of stabilizing system on availability in the law of control data about angle of rotation of steering gear and its velocity is established. Conclusions. It is proven the ability of improvement the stabilizing system by means of inclusion in law of control kinematic parameters of the executive device from the point of view of such performances as a stability factor and energy costs during transient processes.